Effect of Baffle Structure for the Particle Deposition Characteristics of in the Novel Cavity Upstream of the Pre-swirl Nozzles - Y. Wang; G. C. Li; W. Zhang; H. B. He (Journal of Applied Fluid Mechanics)
This study investigates the particle deposition characteristics within a novel cavity featuring a transverse baffle oriented perpendicular to the coolant flow, positioned upstream of the pre-swirl nozzles in the turbine disk cavity. The baffle-induced vortex enhances particle deposition, thereby reducing particle ingress into the turbine disk cavity. Against such a background, a comparative analysis was hereby conducted to delve into the deposition characteristics of particles across four baffle structures. The coolant and particle temperature at the cavity inlet was set at 763.5 K, with a total coolant mass flow rate of 0.2475 kg/s through two impingement holes and an outlet pressure of 2 MPa. The results indicate that the quantity-based deposition rate increases from 66.4% prior to the installation of baffle to 77.2% following the implementation of three baffles. Furthermore, the quality-based deposition rate rises from 14.7% in the absence of baffles to 37.2% following the installation of three baffles. The deposition is primarily concentrated in the target surface area directly opposite the impingement hole, between Baffle 1, and in regions located at 0.5 times the diameter of the impingement hole both upstream and downstream of Baffle 3.